Hybridization of Somatic Cells - Ephrussi, Boris, 1901-1979 (Book collections on Project MUSE., 2015)
Since its discovery in I960, the hybridization of somatic cells has evolved from a biological curiosity into an analytical method that today underlies nearly all investigations of the genetic aspects of various biological phenomena. As an eyewitness to this development from its inception forward, Boris Ephrussi here relates the history of somatic hybridization and the formation of its methodology, lie follows with a discussion of the characteristics and properties of the resultant hybrid cells. Together, these topics comprise an authoritative introduction to the principles of the technique.